Assessing the level of Safety Knowledge Attitude Behaviour (Safety KAB): a case study in a public cleansing firm - Zulkifly, Syazwan Syah; Syed Ismail, Sharifah Norkhadijah; Hasan, Nor Halim; Mahadi @ Othman, Muhammad Razif; Baharudin, Mohd Rafee (FAZ Publishing, 2020)
In Malaysia, utility sector including public cleaning service has a relatively high accident cases recorded in recent years. Exposing to various type of hazards, the workers need to maintain their safety behaviour to prevent workplace accidents. As safety behaviour is found to become the leading factor to work-accidents, this research proposed to examine the level of safety knowledge-attitude-behaviour (safety KAB), plus the effect of safety knowledge and safety attitude on safety behavior amongst workers in a public cleansing company in the southern region of Malaysia. This is a quantitative study involving a cross sectional design where 313 sets of a questionnaire were distributed and answered by to workers who involve in solid waste collecting and public cleansing works from Company X. The level of safety KAB was determined by the mean values derived from the descriptive analyses, while the direct effect to the variables were tested using PLS-SEM modelling. The results indicated that the level of safety attitude and safety behaviour is high, whereas safety knowledge is at a moderate level. These findings indicated the positive results of safety intervention conducted by the government towards Company X as well as the initiative programs conducted by the company. Furthermore, the PLS-SEM analysis determined that safety attitude and safety knowledge had a significant effect on safety behavior. Hence, the present research suggests alternative structural model, which deemed appropriate for Malaysia’s public cleansing organizations, and offers a predictive model of safety knowledge, safety attitude, and safety behaviour for future research. Lastly, the outcome this study is also hoped to serve as a useful reference to the related industry for elevating safety KAB among the workers.